STRUCTURAL SYNTHESIS OF DYNAMIC INFORMATION SYSTEMS - Antoschuk, Svetlana; Maevsky, Dmitry (International Journal of Computing, 2014)
Theoretical bases are considered and the method of synthesis of the dynamic information systems structure is created with a capacity for adaptation at the changes of a subject domain. A capacity for adaptation is provided due to the selection of a variation part of algorithms of the system that changing at the changing the subject domain. The variation part of algorithms is kept in the database of the system that provides their rapid replacement and promotes a fail safety on the stage of exploitation.